Transportation systems in buildings : CIBSE guide D: 2015. (CIBSE, 2015)
This 5th Edition of CIBSE Guide D is the result of extensive review and revision by a dedicated and enthusiastic team comprising lift and escalator specialists and building service engineers. This Guide is very comprehensive, covering the whole spectrum of interior circulation, planning and design, selection of equipment and performance, computer programmes, types of systems, legislation, fire and safety, requirements for persons with disabilities, lift components, lift traffic controls, escalators and moving walkways (passenger conveyors), energy consumption, electrical systems and environmental conditions. The purpose of Guide D is to provide guidance to practitioners involved in such systems. The Guide should also be of interest to architects and developers, along with facilities and building managers who may not be directly concerned with the design and installation of lifts and escalators but need to understand the advice offered to them by specialists.